2021
DOI: 10.3389/fneur.2021.642604
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological Changes in the Enteric Nervous System of Rotenone-Exposed Mice as Early Radiological Markers for Parkinson's Disease

Abstract: Parkinson's disease (PD) is known to involve the peripheral nervous system (PNS) and the enteric nervous system (ENS). Functional changes in PNS and ENS appear early in the course of the disease and are responsible for some of the non-motor symptoms observed in PD patients like constipation, that can precede the appearance of motor symptoms by years. Here we analyzed the effect of the pesticide rotenone, a mitochondrial Complex I inhibitor, on the function and neuronal composition of the ENS by measuring intes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 33 publications
(42 reference statements)
0
13
0
Order By: Relevance
“…Risk factors, such as gene mutations (α-syn, parkin), brain injury, stress, and pesticide exposure, are also linked to PD [ 7 ]. Although the origin of PD is not fully understood, recent studies showed that the non-motor symptoms—particularly GI dysfunction—manifest before the premotor phase of PD and may contribute to PD pathogenesis via the gut–brain axis [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors, such as gene mutations (α-syn, parkin), brain injury, stress, and pesticide exposure, are also linked to PD [ 7 ]. Although the origin of PD is not fully understood, recent studies showed that the non-motor symptoms—particularly GI dysfunction—manifest before the premotor phase of PD and may contribute to PD pathogenesis via the gut–brain axis [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…This animal model also showed at least one non-motor symptom associated with PD (i.e. constipation), which was related to the loss of sympathetic and parasympathetic innervation of the intestinal tract 13,14 .…”
Section: Gfpmentioning
confidence: 85%
“…The prevalence of non-motor symptoms is as a whole equally consistent, however there is a high variability and inconsistency regarding the type of non-motor symptoms that PD-patients present and the type of neurons responsible for each symptom. For example, the prevalence of constipation is of 46.5% (range: 27.5–71.7%) for which alterations in cholinergic and sympathetic neurons as well as enteric neurons has been described 13 , 14 , 38 . In the case of the REM sleep behaviour disorder (RBD) the prevalence is of 34.2% with (range: 29.6–38.7%) and current research suggests that neuronal degeneration of brainstem nuclei, including the pontine tegmental area and medulla, is the pathophysiological cornerstone of RBD 7 , 39 .…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of non-motor symptoms is as a whole equally consistent, however there is a high variability and inconsistency regarding the type of non-motor symptoms that PD-patients present and the type of neurons responsible for each symptom. For example, the prevalence of constipation is of 46.5% (range: 27.5–71.7%) for which alterations in cholinergic and sympathetic neurons as well as enteric neurons has been described [13, 14, 46]. In the case of the REM sleep behaviour disorder (RBD) the prevalence is of 34.2% with (range: 29.6–38.7%) and current research suggests that neuronal degeneration of brainstem nuclei, including the pontine tegmental area and medulla, is the pathophysiological cornerstone of RBD [7, 47].…”
Section: Discussionmentioning
confidence: 99%
“…This animal model also shows at least one non-motor symptom associated with PD (i.e. constipation), which was related to the loss of sympathetic and parasympathetic innervation of the intestinal tract [13, 14].…”
Section: Introductionmentioning
confidence: 99%